Discourse of Asceticism: A Critical Textual Analysis and Social-Identity Practices in Pesantren - Lutfitasari, Wevi; Mujtahidin, Mujtahidin; Vidiarama, Made Arya (el Harakah: Jurnal Budaya Islam, 2025)
The discourse of asceticism functions as a distinctive identity that reflects the idealization of pesantren life, rooted in a high level of spirituality. Previous studies have explored pesantren traditions from various angles but none have provided a holistic account of asceticism within pesantren. This research offers novelty by analyzing ascetic traditions through both discourse and social practice, highlighting how santri’s interaction with their social environment shapes and sustains these values. This study aims to present expressions of asceticism within linguistic discourse and to describe its dimensions in pesantren traditions as reflections of that discourse. This research is categorized as descriptive qualitative research, employing Fairclough's conception of discourse theory, focusing on both the textual level and the dimension of social practice. Two key findings emerge: first, the linguistic characteristics of the three pesantren reflect asceticism through calligraphy and Islamic advice, promoting spiritual deepening, socio-spiritual relationships, the strengthening of faith and reliance on God, the development of intellect and character, self-restraint from materialism, and a simple way of life.. Second, the dimension of asceticism in the pesantren tradition is reflected in spiritual practices and a distinctive lifestyle, such as concentration on God, affirmation of monotheism, love for the Prophet Muhammad, self-restraint from arrogance, and the creation of harmony through self-discipline. In conclusion, within the pesantren tradition, the conception of ascetic discourse is expressed through linguistic discourse that reflects the distinctive aspects of pesantren life in deepening Islamic spirituality and embracing simplicity. Further studies are needed to compare the varying ascetic traditions practiced in pesantren across different regions. In addition, conducting surveys with santri would help reveal their perspectives on how linguistic discourse shapes and influences these ideals. Wacana asketisme berfungsi sebagai identitas khas yang mencerminkan idealisasi kehidupan pesantren, yang berakar pada aspek spiritualitas tinggi. Kajian sebelumnya telah meneliti tradisi pesantren dari berbagai sudut namun belum ada yang memberikan gambaran menyeluruh tentang asketisme dalam pesantren. Penelitian ini menawarkan kebaruan dengan menganalisis tradisi asketis melalui perspektif wacana dan praktik sosial, serta menyoroti bagaimana interaksi santri dengan lingkungan sosialnya membentuk dan mempertahankan nilai-nilai tersebut. Penelitian ini bertujuan untuk menyajikan ekspresi-ekspresi asketisme dalam diskursus linguistik dan mendeskripsikan dimensinya dalam tradisi pesantren sebagai refleksi dari diskursus tersebut. Penelitian ini tergolong penelitian kualitatif deskriptif dengan mengambil konsepsi Fairclough tentang teori wacana kebahasaan pada tataran tekstual dan dimensi praktis sosial. Dua temuan utama muncul: Pertama, karakteristik linguistik di tiga pesantren mencerminkan ekspresi asketisme yang berasal dari seni kaligrafi dan nasihat Islam. Wacana ini menyampaikan rekomendasi untuk memperdalam hubungan spiritual dengan Allah, hubungan sosial-spiritual, keimanan dan tawakal, pengembangan intelektualitas dan akhlak, pengendalian diri terhadap materialisme, dan kesederhanaan hidup. Kedua, dimensi asketisme dalam tradisi pesantren terwujud dalam praktik-praktik spiritual dan gaya hidup yang khas. Dimensi-dimensi ini mengarah pada fenomena seperti latihan konsentrasi yang diarahkan kepada Allah, praktik yang menegaskan keesaan Allah, mencintai Rasulullah sebagai bagian dari rukun iman, pengendalian diri terhadap kesombongan, serta upaya untuk menciptakan keharmonisan melalui saling mengatur diri. Sebagai kesimpulan, dalam tradisi pesantren, konsepsi wacana asketisme diekspresikan melalui wacana linguistik yang berisi kekhasan kehidupan pesantren dalam memperdalam spiritualitas islami dan kesederhanaan. Penelitian lebih lanjut diperlukan untuk membandingkan berbagai tradisi asketis yang dipraktikkan di pesantren di berbagai daerah. Selain itu, pelaksanaan survei terhadap para santri akan membantu mengungkap perspektif mereka mengenai bagaimana wacana kebahasaan membentuk dan memengaruhi ideal-ideal tersebut.